Pengaruh Kompensasi, Lingkungan Kerja Dan Penghargaan Atas Prestasi Kerja Terhadap Kinerja Karyawan Di PT. Asuransi ASEI Indonesia Unit Syariah Cabang Pekanbaru - Jeli Nata Liyas (STIE Mandala Jember, 2019)
The purpose of this research is to know the influence of compensation, work environment and reward for high performance against the performance of employees at PT. Asuransi Asei Indonesia Unit Syariah cabang Pekanbaru. Analysis of data used is the analysis of the regression of the linear risks. The sample of this study as many as 55 of the respondents who is a permanent employee at PT. Asuransi Asei Indonesia Unit Syariah cabang Pekanbaru. Variables are used is compensation, work environment and reward for high performance. The results showed that these three variables tested simultaneously have a significant effect on the performance of employee at PT. Asuransi ASEI Indonesia Unit Syariah cabang Pekanbaru. In partial compensation significantly influences, while the work environment and reward for high performance does not affect the significant. Variables are compensation, work environment and reward for high performance of influential 79% of employee performance, while the rest of the 21% affected by variables not included in research.